PELESTARIAN LINGKUNGAN MELALUI PERIKLANAN KREATIF: SEBUAH PENDEKATAN EKOLOGI (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2016)
Environment is the place where humans rely their life on. Uncontrolled environment exploration and exploitation causes the damage on the environment itself, also reduce the environment's ability to support and to accommodate in fulfilling human's decreasing needs. Based on ecology study, environment's preservation is needed to take care and maintain the availability of natural resources in fulfilling human's needs. One way can be used in order to invest the environment preservation principles is by using advertisement media. The use of creative advertisement is expected to be able to influence and change community's mindset to be wiser and more effective in using environment, also by orienting on preservation principles. One of technology advancement, internet, has been influencing the marketing of communication so then it makes is easier to invest preservation principles among communities. Internet advancement boosts many related institution to be unceasingly giving creative advertisement relating to environment preservation. The concept of creative advertisement is carried by institution as the support to government for continue development. Green Marketing (environmentally friendly marketing) as the form of institution active role implementation on environment preservation is expected to be able to influence communities to join together in preserving environment.Â Key words: Creative Advertisement, Environment Preservation, Ecology, Green Marketing